Modelling of nonstationary heat conduction problems in micro-periodic composites using homogenisation theory with corrective terms - Lefik, M.; Schrefler, B.A. (Archives of Mechanics, 2000)
Homogenisation based on the asymptotic series expansion is used to model a nonstationary behaviour of a rigid heat conductor with micro-periodic structure. A usual first-order approximation (which cannot be assumed as a satisfactory solution for time-dependent problems) is treated as a suitable starting point for further corrections that make it admissible. An initial correction takes into account some fast processes acting on the level of the microstructure and guarantees that the initial condition is satisfied. Some higher-order correctors are intended to improve the first-order approximation far from the onset of the process, for composites with strongly different properties of components or for the case of a rough microstructure. A numerical example shows that the role of the initial corrector is prevailing in the model.